Office equipment inventory system / Teh Meng Hai - Teh, Meng Hai (2001)
This report was based on the final year project as a partial requirement for the degree of information technology. It’s describing the office equipment inventory system that will be developing. This report contains 4 chapters which are introduction of the project, literature review, methodology and system analysis and system design. Office equipment inventory system is a sub system of the e-Faculty project. e-Faculty project is a project that will bring faculty science computer and information technology to the electronic era. The objective of e-Faculty is to bring faculty become an electronic effective faculty. The purpose of develop the office equipment inventory system is to computerized the inventory system which is still manage and develop a web-based system that can be used by all the faculty members. With this developed system, staff can manage the inventory information more easily and lectures can apply the stationery inventory through the online system. This report will be describe the system that will be develop methodology that will be use system analysis and the system design.